LINGVOKULTUROLOGIYANING ASOSIY TUSHUNCHAVIY-TERMINOLOGIK APPARATI - Bekiyeva, M.J. (SCIENCE and SOCIETY, 2020)
The article deals with the interpretation of the concepts of linguoculturology, linguocultural paradigm, ethnic mentality and linguocultural conception.